Russia’s hybrid invasion in Belarus during the presidential election campaign 2020 - Ilyina, Anastasiya (Eastern Review, 2020)
There are various instruments for Russia to have influence on its neighbours, such as using opinion leaders (authorities), intellectuals, and journalists to create a favourable informational context or to place the ordered materials in the media so as to have an impact on public opinion. These are the types of information attacks that can lead to the loss of statehood or the substantial limitation of sovereignty. This hybrid aggression strives to precisely this result. The main questions are: how the Russian information space, mud-slinging and troll farms functioned in Belarus during the presidential election? How the fake news which is produced in Russia impacts societies? Which political scenarios appeared in Belarus following Russia’s informational influence? It is a fact that today the Russian authorities use tools of fake news and propaganda; combined with the extra possibilities of social media. The appearance of fake news is connected with national safety because they jeopardize democratic institutions, lead to the radicalization of society, and change the balance of authority. In the research, the methodologies were used from the sociology of communication, political science and content analysis.